2022
DOI: 10.1002/mar.21637
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the antecedents of green and sustainable purchase behaviour: A comparison among different generations

Abstract: This paper investigates whether generation matters in the intention to buy green and sustainable products and, simultaneously, examines the antecedents of green and sustainable buying behaviour among three different generational cohorts (X, Y, and Z). By doing this, the present paper fills the gap regarding studies addressing the relationships between age and sustainable behaviour which have not included actual green and sustainable buying intention, along with the gap regarding studies only focussing on one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 57 publications
(134 reference statements)
0
39
0
3
Order By: Relevance
“…Lastly, consumers' pursuit of sustainable consumption would depend on a lot of factors other than physical activity, such as their socioeconomic status (Kim et al, 2022), narcissism and faith in humanity (Bowen et al, 2022), generational cohort (Casalegno et al, 2022), and mindfulness (Kaur & Luchs, 2021). The integration of such consumer‐related factors that shape sustainable consumption along with physical activity should be pursued by future research.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Lastly, consumers' pursuit of sustainable consumption would depend on a lot of factors other than physical activity, such as their socioeconomic status (Kim et al, 2022), narcissism and faith in humanity (Bowen et al, 2022), generational cohort (Casalegno et al, 2022), and mindfulness (Kaur & Luchs, 2021). The integration of such consumer‐related factors that shape sustainable consumption along with physical activity should be pursued by future research.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Nejad et al (2015) and, more recently, Bu et al (2022) have observed a high degree of homophily, defined as “contact between similar people [which] occurs at a higher rate than among dissimilar people” on social networks (McPherson et al, 2001). This is true across generations and affects aspects as consumer behaviour (Casalegno et al, 2022) and social networks' building (Ballestar et al, 2016). Notably, in the general polarisation between activists and deniers, Twitter provides an “echo chamber” in which individuals interact with like‐minded people, creating communities dominated by a single approach.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Generally, each generation of the population has its own specificities, especially in the green and sustainable area (Casalegno et al, 2022;Ham et al, 2021). However, we do not know how each generation behaves in the sharing economy environment concerning their willingness to supply and demand unused assets.…”
Section: Introductionmentioning
confidence: 99%